Hydrocarbon potential and palaeodepositional environment of subsurface sediments of the Anambra basin, south eastern Nigeria (2014)
Subsurface core samples obtained from Enugu 1325 and 1331 wells within the Anambra Basin were characterized by standard organic geochemical methods; Rock-eval and GC-Ms; to deduce the hydrocarbon potential, source input of the organic matter and palaeodepositional environment of the basin. The lithologies in both wells consist of coals, shales and siltstones and belong to the Mamu Formation. The Total Organic Carbon (TOC), Soluble Organic Matter (SOM) and Genetic Potential (GP) of the core samples ranged from 1.59 – 70.33wt%., 238.1 – 4095.2 ppm, 2.34 - 177.36 respectively. These values indicate that the source rock is moderately to fairly rich in organic matter. A cross plot of hydrocarbon potential versus TOC, EOM versus TOC, indicated that the source rock is Type III and gas prone. Tmax values range from 426 – 435ºC which indicate low maturation level for the source rock. The ratios of βα/αβ C29 hopane, βα/αβ C30 hopane, and 22S/22S+22R C32 hopane ranged from 0.32 to 0.57; 0.20 to 0.59; and 0.49 to 0.56 respectively, suggesting immature organic matter. A cross plot of hydrogen index (HI) versus Tmax, production index (PI) versus Tmax, both suggest that the source rock is immature. Further maturity parameters such as MPI-1 (Methyl Phenanthrene Index), MDR (Methyl Dibenzothiophene Ratio), and Rm (calculated vitrinite reflectance), revealed ranges of 0.14-0.76, 0.99-4.21, and 0.62-0.82 respectively. These indicate that the samples are immature to marginally mature. High values were obtained from the C24 tetracyclic/C24 tricyclic terpanes and the C19/C20 tricyclic terpane ratios, (1.54-2.25) and (0.74-1.34) respectively, which are indicative of terrigenous organic matter. The dominance of C29 over C28 and C27 indicate higher terrigenous input. The pristane/phytane ratio of 5.08 to 8.97 indicates oxic condition of deposition for the sediments. The results show that the sediments were deposited in oxic to suboxic environment with moderately to fairly rich organic matter of substantial terrigenous input. The source rock has the potential to generate gas rather than oil, given sufficient maturity